2006
DOI: 10.2337/db06-0016
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor α Improves Pancreatic Adaptation to Insulin Resistance in Obese Mice and Reduces Lipotoxicity in Human Islets

Abstract: Peroxisome proliferator-activated receptor (PPAR) ␣ is a transcription factor controlling lipid and glucose homeostasis. PPAR␣-deficient (؊/؊) mice are protected from high-fat diet-induced insulin resistance. However, the impact of PPAR␣ in the pathophysiological setting of obesityrelated insulin resistance is unknown. Therefore, PPAR␣ ؊/؊ mice in an obese (ob/ob) background were generated. PPAR␣ deficiency did not influence the growth curves of the obese mice but surprisingly resulted in a severe, age-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 38 publications
1
88
0
2
Order By: Relevance
“…Moreover, recent studies show that PPAR-␣ deficiency decreases the mean area of the pancreatic ␤-cells and diminishes insulin secretion in response to glucose, whereas PPAR-␣ agonists reduce lipotoxicity in human islets and prevent the progression to diabetes (19). It is therefore possible that the pancreatic effects of PPAR-␣ are responsible for the results observed in our study.…”
Section: Discussionsupporting
confidence: 30%
“…Moreover, recent studies show that PPAR-␣ deficiency decreases the mean area of the pancreatic ␤-cells and diminishes insulin secretion in response to glucose, whereas PPAR-␣ agonists reduce lipotoxicity in human islets and prevent the progression to diabetes (19). It is therefore possible that the pancreatic effects of PPAR-␣ are responsible for the results observed in our study.…”
Section: Discussionsupporting
confidence: 30%
“…In rats, it was observed that activation of PPARα for 24 h can reverse the insulin hypersecretion induced by high-fat feeding [23]. In ob/ob mice, glucose intolerance is aggravated by the absence of PPARα, correlating with reduced glucose-stimulated insulin secretion in isolated islets [21]. The same study reported that PPARα agonists protected human islets from palmitateinduced lipotoxicity [21].…”
Section: Introductionmentioning
confidence: 65%
“…In ob/ob mice, glucose intolerance is aggravated by the absence of PPARα, correlating with reduced glucose-stimulated insulin secretion in isolated islets [21]. The same study reported that PPARα agonists protected human islets from palmitateinduced lipotoxicity [21]. In pregnant rats fed a high-fat diet, in vivo administration of a PPARα agonist has been shown to prevent loss of glucose-stimulated insulin secretion [24].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Identification of the location of triacylglycerol within the pancreas has been hampered by rapid postmortem autolysis, but a study of pancreata retrieved and not used for pancreas transplantation showed that intracellular fat droplets were widely distributed within the exocrine cells, in addition to widely scattered isolated adipocytes (23). Exposure to even modest concentrations of fatty acids causes marked triacylglycerol accumulation in human islets in vitro (7). Local lipolysis is likely to bring about interstitial and intracellular concentrations of fatty acids sufficient to inhibit b-cell function.…”
Section: Discussionmentioning
confidence: 99%